A study on leadership skills and its relation towards employee engagement: finding from the Ministry of Health in Malaysia / Iffa Nadhira Abdul Hakim and Dina Aida Shaari - Abdul Hakim, ffa Nadhira; Shaari, Dina Aida (2022)
In recent years, numerous reports revealed that the decreasing level employee engagement within the organizations has been a huge concern that needs to be resolved. Leadership skills possessed by the organizations’ leaders are reported to have a huge impact on the employees' well-being. This study was conducted to study leadership skills and its relations towards employee engagement of employees in the Ministry of Health Malaysia. The leadership skills observed in this study are Conceptual skills, Interpersonal skills, Communication skills, and Technical skills. As such, 116 respondents have been involved in this study. The level of employee’s engagement in the Ministry of Health and the relationship between the leadership skills involved in this study and employee engagement were examined. Results suggested that the level of employee engagement in the Ministry of Health is high and all the leadership skills involved in this study namely, Conceptual skills, Interpersonal skills, Communication skills, and Technical skills are positively correlated with employee engagement. Based on the research findings, the most significant predictor of leadership skills toward employee’s engagement is Conceptual skills with a high beta value (ß=0.492, p=0.001).